METHYLATION OF SEROTONIN RECEPTOR 3A IN ADHD, BORDERLINE PERSONALITY, AND BIPOLAR DISORDERS: LINK WITH SEVERITY OF THE DISORDERS AND CHILDHOOD MALTREATMENT. Issue 1 (9th September 2015) - Perroud, Nader; Zewdie, Seblewongel; Stenz, Ludwig; Adouan, Wafae; Bavamian, Sabine; Prada, Paco; Nicastro, Rosetta; Hasler, Roland; Nallet, Audrey; Piguet, Camille; Paoloni‐Giacobino, Ariane; Aubry, Jean‐Michel; et al.
Abstract : Background: Serotonin 3A receptor (5‐HT3A R) is associated at the genetic and epigenetic levels with a variety of psychiatric disorders and interacts with early‐life stress such as childhood maltreatment. We studied the impact of childhood maltreatment on the methylation status of the 5‐HT3A R and its association with clinical severity outcomes in relation with a functional genetic polymorphism. Methods: Clinical severity indexes of 346 bipolar, borderline personality, and adult attention deficit hyperactivity disorders patients were tested for association with the DNA methylation status of eight 5‐HT3A R gene CpGs. Relationship between the functional variant rs1062613 (C > T) and methylation status on severity of the disorders were also assessed. Results: Childhood maltreatment was associated with higher severity of the disease (higher number of mood episodes, history of suicide attempts, hospitalization, and younger age at onset) across disorders and within each individual disorder. This effect was mediated by two 5‐HT3A R CpGs. Compared to T allele carriers, CC carriers had higher methylation status at one CpG located 1 bp upstream of this variant. Conclusions: This study shows that epigenetic modification of the 5‐HT3A R is involved in the mechanism underlying the relationship between maltreatment in childhood and the severity of several psychiatric disorders in adulthood.